1992
DOI: 10.1038/358152a0
|View full text |Cite
|
Sign up to set email alerts
|

Objective analysis of the topological organization of the primate cortical visual system

Abstract: The primate cortical visual system is composed of many structurally and functionally distinct areas, each receiving and sending about 10 projections from and to other cortical areas. The visual cortex is thus served by many cortico-cortical connections to form a network of considerable complexity. Thus the gross organization of this cortical processing system presents a formidable topological problem: although the spatial position of the areas in the brain is reasonably well established, the gross 'processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
296
1
14

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 439 publications
(331 citation statements)
references
References 20 publications
19
296
1
14
Order By: Relevance
“…What are the potential functional implications of this mode of connectivity? The connectivity clusters found in cat and rhesus monkey cortex tend to follow functional subdivisions of these brains [32,38]. The groups of areas delineated by clustering are also broadly similar to clusters of semi-functional, neuronographic interactions [67].…”
Section: And Global Network Designmentioning
confidence: 72%
See 1 more Smart Citation
“…What are the potential functional implications of this mode of connectivity? The connectivity clusters found in cat and rhesus monkey cortex tend to follow functional subdivisions of these brains [32,38]. The groups of areas delineated by clustering are also broadly similar to clusters of semi-functional, neuronographic interactions [67].…”
Section: And Global Network Designmentioning
confidence: 72%
“…For example, streams of visual cortical areas have been identified that are segregated functionally [37] as well as in terms of their inputs, outputs and mutual interconnections [38]. Topological sequences of areas might provide the layout for signaling pathways across cortical networks [39].…”
Section: Large-scale Connection Patternsmentioning
confidence: 99%
“…Thus, it is tempting to conclude that highly complex pyramidal cells in the dorsolateral gPFC is a characteristic of the latter species, which may differ from that in other primates that diverged earlier, such as New World monkeys and the great apes. Alternatively, the apparent species differences may reflect regional variation in neuronal maturation rates (Jacobs and Scheibel, 1993; Jacobs et al, 1995, 1997; Page et al, 2002; Duan et al, 2003; Elston et al, 2009, 2010a,b) or arise through sampling different subsets of projection neurons in the different cortical areas, which have been shown to differ in both their morphology (Schofield et al, 1987; Hallman et al, 1988; Hübener and Bolz, 1988; de Lima et al, 1990; Hübener et al, 1990; Einstein, 1996; Matsubara et al, 1996; Duan et al, 2002; Soloway et al, 2002; Elston and Rosa, 2006) and density (Jones and Powell, 1970; Barbas, 1992; Young, 1992; Pandya and Yeterian, 2000; Petrides, 2000; Collins et al, 2005) in different cortical areas. In either case, the result is consistent with our main conclusion that pyramidal cells develop differently among cortical areas and mature into specialized circuits.…”
Section: Discussionmentioning
confidence: 99%
“…The gaze cue to spatial position effectively improved the response to a spatial property of the target. The STS region, including the gaze detector, has connections with both the dorsal and ventral pathways (Young, 1992). These two visual pathways have also been characterized as the "action" and "recognition" pathways (Goodale & Milner, 1992).…”
Section: Discussionmentioning
confidence: 99%